Decreased interhemispheric functional connectivity in insula and angular gyrus/supramarginal gyrus: Significant findings in first-episode, drug-naive somatization disorder. (28th February 2016) - Su, Qinji; Yao, Dapeng; Jiang, Muliang; Liu, Feng; Long, Liling; Dai, Yi; Yu, Miaoyu; Zhang, Zhikun; Zhang, Jian; Liu, Jianrong; Xiao, Changqing; Zhao, Jingping; et al.
Abstract: Neuroimaging data have demonstrated brain functional alterations in patients with somatization disorder (SD). However, there is little information on interhemispheric resting-state functional connectivity (FC) in SD. In this study, resting-state functional magnetic resonance imaging (fMRI) and voxel-mirrored homotopic connectivity (VMHC) were applied to examine the changes of interhemispheric FC of the whole brain in patients with SD. A total of 25 first-episode, medication-naive SD patients and 28 age-, sex-, education-matched healthy controls (HC) underwent resting-state fMRI, and the data were analyzed by VMHC. Compared with HC, patients had lower VMHC in the angular gyrus/supramarginal gyrus (AG/SG) and insula. The reproducibility of the results was validated using the split-half and leave-one-out validations. No significant correlation was found between the VMHC in AG/SG or insula and clinical variables. Our findings indicate that the interhemispheric FC in the AG/SG and insula is decreased in first-episode, treatment-naive patients with SD, and thus provide new insight for disruption of interhemispheric FC in the pathophysiological mechanism of SD. Highlights: VMHC, a validated method, was used to investigate the interhemispheric FC. Decreased VMHC in AG/SG and insula were found in SD patients. AG/SG and insula may be important brain regions for the pathophysiology of SD. SD patients enrolled were first episode, drug-naive individuals.